Control of photoelectron momentum distributions by bichromatic polarization-shaped laser fields. (20th October 2017) - Kerbstadt, Stefanie; Pengel, Dominik; Johannmeyer, Daniela; Englert, Lars; Bayer, Tim; Wollenhaupt, Matthias
Abstract: Bichromatic polarization-shaped femtosecond laser pulses are used to control three-dimensional photoelectron momentum distributions (3D-EDs) from resonance enhanced multi-photon ionization of potassium atoms. The light fields consisting of two spectral bands with different ellipticity are produced using an ultrafast polarization pulse shaper equipped with a custom polarizer in the Fourier plane. The tomographically reconstructed 3D-EDs from ionization with counterrotating circularly or orthogonal linearly polarized bichromatic laser pulses show different angular momentum superposition states at four distinct photoelectron energies. The analysis of the measured 3D-EDs reveals that the underlying physical mechanism is based on the interplay of ionization pathway selection via quantum mechanical selection rules for optical transitions and intrapulse frequency mixing of the spectral bands with different ellipticity.